Study on engine pylon emergency separation design of civil aircraft - CHEN Haihuan; LI Zejiang; CHEN Shaokai (Hangkong gongcheng jinzhan, 2023)
Engine pylon emergency separation is one of the key technologies in civil aircraft design, which is difficult to obtain from abroad.Domestic researches are mainly about theories and thoughts, which cannot be applied on engineering.In this paper, the research on relationship of design loads among pylon, fuse pin and wingbox is carried out based on airworthiness standards.Load determination methods for strength calculation of interface structures is proposed through scenario analysis.The results show that the engine pylon emergency separation design only needs to consider predominantly upward loads and aft loads separately.Giving reasonable relationship of design loads among pylon, fuse pin and wingbox can reduce the weight of structures.Load directions of components connecting the pylon to the wing should be determined through scenario analysis considering structural details.